A Sticky Situation: Variable Agreement Between Platelet Function Tests Used to Assess Anti-platelet Therapy Response - Nakahara, Hirotomo; Sarker, Tania; Dean, Christina L.; Skukalek, Susana L.; Sniecinski, Roman M.; Cawley, C. Michael; Guarner, Jeannette; Duncan, Alexander; Maier, Cheryl L. (Frontiers in Cardiovascular Medicine, 2022)
Background Platelet function testing to monitor antiplatelet therapy is important for reducing thromboembolic complications, yet variability across testing methods remains challenging. Here we evaluated the agreement of four different testing platforms used to monitor antiplatelet effects of aspirin (ASA) or P2Y12 inhibitors (P2Y12-I). Methods Blood and urine specimens from 20 patients receiving dual antiplatelet therapy were analyzed by light transmission aggregometry (LTA), whole blood aggregometry (WBA), VerifyNow PRUTest and AspirinWorks. Result interpretation based on pre-defined cutoff values was used to calculate raw agreement indices, and Pearson's correlation coefficient determined using individual units of measure. Results Agreement between LTA and WBA for P2Y12-I-response was 60% (r = 0.65, high-dose ADP; r = 0.75, low-dose ADP). VerifyNow agreed with LTA in 75% (r = 0.86, high-dose ADP; r = 0.75, low-dose ADP) and WBA in 55% (r = 0.57) of cases. Agreement between LTA and WBA for ASA-response was 45% (r = 0.09, high-dose collagen WBA; r = 0.19, low-dose collagen WBA). AspirinWorks agreed with LTA in 60% (r = 0.32) and WBA in 35% (r = 0.02, high-dose collagen WBA; r = 0.08, low-dose collagen WBA) of cases. Conclusions Overall agreement varied from 35 to 75%. LTA and VerifyNow demonstrated the highest agreement for P2Y12-I-response, followed by moderate agreement between LTA and WBA. LTA and AspirinWorks showed moderate agreement for aspirin response, while WBA showed the weakest agreement with both LTA and AspirinWorks. The results from this study support the continued use of LTA for monitoring dual antiplatelet therapy, with VerifyNow as an appropriate alternative for P2Y12-I-response. Integration of results obtained from these varied testing platforms with patient outcomes remains paramount for future studies.